New approach to targeting feed options at scale in East Africa using global data sets - CGIAR Research Program on Livestock (2021)
Version 2.0.0 of the FEAST Global Data Repository was developed with three priorities in mind – data integrity, functionality and extendibility. The focus on data integrity means that all data cleaning and spatial additions have been built in a way that leaves the raw data untouched in a secure database.